2006
DOI: 10.1177/230949900601400122
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty Infected by Brucella: A Report of Two Cases

Abstract: daily were prescribed. At 5.5-year and 5-year followup, respectively, both patients were asymptomatic and free of infection with well-integrated implants. As the Brucella pathogen is highly susceptible to antibiotics, standard 2-stage revision arthroplasty for loosened implant or debridement and antibiotic treatment for well-fixed implant should suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…After removal of duplicates, 47 remained. 18 reports contained data on 23 patients with 26 Brucella -related prosthetic joint infections; only 3 were in returning travellers [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21]. Table 1 summarises all 24 patients including: gender, country of exposure, type of implant and time to symptom onset.…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, 47 remained. 18 reports contained data on 23 patients with 26 Brucella -related prosthetic joint infections; only 3 were in returning travellers [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21]. Table 1 summarises all 24 patients including: gender, country of exposure, type of implant and time to symptom onset.…”
Section: Resultsmentioning
confidence: 99%
“…Sacroiliac joint is the most common site of involvement [ 7 ], followed by knee or ankle joints [ 8 ]. Monoarthritis of the hip in children [ 9 ] and even prosthetic hip infections [ 10 ] caused by Brucella e have been previously reported, but rarely in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical debridement, retention of implant, and antibrucella therapy were performed in one patient. 7 Six patients were treated with antibrucella treatment only. The mean duration of antibiotic therapy for all patients was 5.8 months.…”
Section: Resultsmentioning
confidence: 99%
“…Most authors suggested a minimum duration of antibrucella therapy of 6 weeks. 7 , 8 , 18 , 19 There is no evidence that a shorter period of antibrucella treatment will give the same results. In our pooled analysis, the mean duration of antifungal therapy was 5.8 months (range 6 weeks–26 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation